Ceramic Proppants Based On High-Ferrous Bauxite - T.D. Dzhienalyev, A.A. Biryukova (International Journal of Advanced Science and Technology, 2019)
The possibility of obtaining ceramic proppants from high-ferrous bauxite of Kazakhstan with properties that meet the requirements of American Petroleum Institute standards was studied. High-ferrous bauxite content in mixtures with refractory clay provides a hardening effect by increasing the content of the crystalline phase in the firing products. This is due to the binding of free silica and other impurities to alumina into secondary mullite and spinel compounds. Proppants with a bulk density of 1.65-1.69 g/cm3, roundness of 0.7, sphericity of 0.9 and crush resistance at 52 MPa of 9.8% were obtained from high-ferrous bauxite and refractory clay mixtures.